A novel differential evolution algorithm for a flange coupling using ANSYS simulations - Ji, Yaofeng; Lu, Qingbo (Frontiers in Materials, 2022)
An novel modified multi-objective differential evolution algorithm was proposed to minimize material mass and margin strength of a flange couplings optimization system. Chaos operator was used to calculate the scaling factor of differential evolution algorithm for the reduction of user participation. Finite element simulation was facilitated to validate the effectiveness of the modified evolution algorithm. Results demonstrate that the structural dimensions influenced material mass more evidently than performance. Hence, this study verifies the feasibility of the modified evolution algorithm for multi-objective optimization on non-standard flange couplings in mechanical industry.